HDAC1 and HDAC2 Are Involved in Influenza A Virus-Induced Nuclear Translocation of Ectopically Expressed STAT3-GFP - Jessica Leong; Matloob Husain (Viruses)
Influenza A virus (IAV) remains a pandemic threat. Particularly, the evolution and increased interspecies and intercontinental transmission of avian IAV H5N1 subtype highlight the importance of continuously studying the IAV and identifying the determinants of its pathogenesis. Host innate antiviral response is the first line of defense against IAV infection, and the transcription factor, the signal transducer and activator of transcription 3 (STAT3), has emerged as a critical component of this response. Also, histone deacetylase 1 (HDAC1) and HDAC2 have been identified as important components of IAV-induced host innate antiviral response. Upon IAV infection, STAT3 is activated and translocated to the nucleus to initiate the transcription of innate response genes. Also, the HDAC1 and HDAC2 are localized to the nucleus. In this study, we sought to investigate the role of HDAC1 and HDAC2 in IAV-induced STAT3 nuclear translocation. We employed a quantitative confocal microscopy approach and analyzed the nuclear translocation of plasmid-expressed STAT3-GFP in IAV-infected cells depleted with the expression of HDAC1 or HDAC2. We found that the depletion of both HDAC1 and HDAC2 expression inhibits the IAV-induced nuclear translocation of STAT3-GFP. These findings will help elucidate the significance of the emerging role of acetylation in IAV infection and disease severity.